PENGARUH LOKASI TERHADAP KEPUTUSAN BERKUNJUNG DI BLACK CAFE - Ikhsan Ikhsan; Sri Ernawati; Nur Khusnul Hamidah (JOURNAL SAINS STUDENT RESEARCH, 2024)
When visiting, location is the main reason in determining a person's decision to visit. The aim of this research is to determine the influence of location on the decision to visit partially. The type of research is associative. The research instrument uses a questionnaire with a Likert scale. The population used in this research is all consumers who have visited Black Cafe, totaling 150 people. The sample size used in this research was 60 respondents with a sampling technique, namely purposive sampling. Data collection techniques using observation, questionnaires, and literature study. Data analysis techniques by carrying out validity tests, reliability tests, simple linear regression tests, correlation coefficients, determination tests, and t tests. The results of this study show that location does not have a significant effect on the decision to visit Black Cafe.